2013
DOI: 10.1016/j.juro.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Routine Flexible Nephroscopy for Percutaneous Nephrolithotomy for Renal Stones with Low Density: A Prospective, Randomized Study

Abstract: Routine flexible nephroscopy during percutaneous nephrolithotomy was associated with a higher stone-free rate, fewer interventions and less bleeding, especially in patients with low HU density stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…Though in such cases, flexible nephroscope could also be useful as it can reach locations which are in accessible with rigid nephroscope. Routine flexible nephroscopy in addition to PCNL with rigid nephroscope was associated with fewer relook procedures, less bleeding, and a higher stone-free rate, especially in patients with low HU density stones [13]. We do agree with above observation but flexible nephroscopes are unavailable at several centers in developing countries.…”
Section: Discussionsupporting
confidence: 77%
“…Though in such cases, flexible nephroscope could also be useful as it can reach locations which are in accessible with rigid nephroscope. Routine flexible nephroscopy in addition to PCNL with rigid nephroscope was associated with fewer relook procedures, less bleeding, and a higher stone-free rate, especially in patients with low HU density stones [13]. We do agree with above observation but flexible nephroscopes are unavailable at several centers in developing countries.…”
Section: Discussionsupporting
confidence: 77%
“…Six studies [9,10,11,12,13,14,15,16] in this review showed that RIRS with holmium laser was as efficient as PCNL in the treatment of selected cases with larger renal stones. In order to improve the stone clearance rate, we can combine PCNL and flexible ureteroscopy for the treatment of large or complex renal stones [37,38]. Flexible nephrolithotomy with a stone basket can easy reach each calyx, thus improving the stone clearance rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our surgical PCNL technique was described previously [10]. Briefly, following administration of general anesthesia, a 6-F open-ended ureteral catheter was placed in the patient in the lithotomy position to view the anatomy of the collecting system.…”
Section: Methodsmentioning
confidence: 99%